Finding the "Right-Size" Physical Therapy Workforce: International Perspective Across 4 Countries. Issue 10 (1st October 2016) - Jesus, Tiago S.; Koh, Gerald; Landry, Michel; Ong, Peck-Hoon; Lopes, António M.F.; Green, Peter L.; Hoenig, Helen
Abstract : Finding the "right-size" physical therapy workforce is an increasingly important issue, but it has had limited study, particularly across nations. This perspective article provides a comprehensive examination of physical therapy workforce issues across 4 countries (United States, Singapore, Portugal, and Bangladesh), which were deliberately selected to allow consideration of key contextual factors. This investigation provides a theoretical model uniquely adapted to focus on variables most likely to affect physical therapy workforce needs. This theoretical model was used to guide acquisition of public domain data across the respective countries. The data then were used to provide a contextualized interpretation about the physical therapy workforce supply (ie, physical therapists per capita) across the 4 countries in light of the following factors: indicators of physical therapy need, financial and administrative barriers affecting physical therapy access and demand, the proportion of physical therapy graduates (with varying trends over time across the countries), and the role of emigration/immigration in supply inequalities among countries of lower and higher income. In addition, both the physical therapy workforce supply and scope of practice were analyzed in the context of other related professions across the 4 countries. This international comparison indicated that there may not be a "one-size-fits-all" recommendation for physical therapy workforce supply across countries or an ideal formula for its determination. The optimal, country-specific physical therapy workforce supply appears to be affected by discipline-specific health care and contextual factors that may vary across countries, and even within the same country. This article provides a conceptual framework and basis for such contextualized evaluations of the physical therapy workforce.